2016
DOI: 10.1002/jmri.25345
|View full text |Cite
|
Sign up to set email alerts
|

Gadoxetic acid-enhanced MRI for the characterization of hepatocellular carcinoma: A systematic review and meta-analysis

Abstract: 3 J. Magn. Reson. Imaging 2017;45:281-290.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
(135 reference statements)
0
30
0
Order By: Relevance
“…A recent meta‐analysis reported that gadoxetate‐enhanced MRI has the highest overall per‐lesion sensitivity (0.86, 95% confidence interval [CI] 0.81–0.88) and positive predictive value (0.94, 95% CI, 0.91–0.96), compared with contrast‐enhanced ultrasound, CT, and MRI with extracellular contrast agents . Of all the available imaging modalities, MRI with gadoxetate is the most sensitive (sensitivity of 0.84–0.96) for detection of ≤2 cm HCCs . Many of these studies have been done in patients without cirrhosis or with well‐compensated cirrhosis.…”
Section: Potential Advantages Of Gadoxetatementioning
confidence: 99%
“…A recent meta‐analysis reported that gadoxetate‐enhanced MRI has the highest overall per‐lesion sensitivity (0.86, 95% confidence interval [CI] 0.81–0.88) and positive predictive value (0.94, 95% CI, 0.91–0.96), compared with contrast‐enhanced ultrasound, CT, and MRI with extracellular contrast agents . Of all the available imaging modalities, MRI with gadoxetate is the most sensitive (sensitivity of 0.84–0.96) for detection of ≤2 cm HCCs . Many of these studies have been done in patients without cirrhosis or with well‐compensated cirrhosis.…”
Section: Potential Advantages Of Gadoxetatementioning
confidence: 99%
“…An example of a recently published subgroup analysis is presented in Fig. . An alternative is meta‐regression.…”
Section: Updating Systematic Reviewsmentioning
confidence: 99%
“…Systematic reviews, when well reported and performed with methodological rigor, represent valuable summaries of existing evidence about risk factors for specific medical conditions, the effectiveness of interventions, or the performance of medical tests . The Cochrane Collaboration defines a systematic review as “a review of the evidence on a clearly formulated question that uses systematic and explicit methods to identify, select and critically appraise relevant primary research, and to extract and analyze data from the studies that are included in the review.”…”
mentioning
confidence: 99%
See 2 more Smart Citations